2018
DOI: 10.1093/ajcn/nqx022
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood undernutrition increases risk of hearing loss in young adulthood in rural Nepal

Abstract: Early childhood undernutrition is a modifiable risk factor for early adulthood hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…One study 35 found that iron deficiency at birth was associated with abnormal auditory neural maturation, and another study 36 found that adult β-carotene, β-cryptoxanthin, and folate intake were associated with lower hearing loss risk. A study in rural Nepal 37 found an association between childhood undernutrition and adult hearing loss. The undernutrition in that study could be compared with what the Greatest Generation experienced as young adults during the Great Depression and may have had similar associations.…”
Section: Discussionmentioning
confidence: 99%
“…One study 35 found that iron deficiency at birth was associated with abnormal auditory neural maturation, and another study 36 found that adult β-carotene, β-cryptoxanthin, and folate intake were associated with lower hearing loss risk. A study in rural Nepal 37 found an association between childhood undernutrition and adult hearing loss. The undernutrition in that study could be compared with what the Greatest Generation experienced as young adults during the Great Depression and may have had similar associations.…”
Section: Discussionmentioning
confidence: 99%
“…Ability is usually thought to be relatively characteristics or trait. These traits are usually thought of as being either genetically determined or developed through the relatively automatics process in growth and maturation, and they are not easily modifiable by practice or experience, of course, can easily modify by practice or experience Thus, abilities are underlying capabilities that support certain skill (Emmett et al, 2018). Learning motor skills prioritizes the muscle movements, veins, and joints in the body, but help is needed through sensory devices and cognitive processing that involves knowledge and understanding.…”
Section: Gross and Fine Motor Skills Developmentmentioning
confidence: 99%
“…Recent research showed an association between iodine deficiency and hearing loss [1,3]. Although the role of thyroid hormone in auditory development is fairly well established in congenital hypothyroidism and thyroid hormone resistance syndromes, little is known about iodine deficiency in relation to auditory function Population questionnaire studies did not resolve this problem.…”
Section: Discussionmentioning
confidence: 99%
“…John Hopkin's researchers studied 2200 children in Nepal, who were undernourished during their preschool years. They found that those who were undernourished in their preschool years were about twice as likely to have hearing loss 16 years later than those who were better nourished as young children [3]. Previous studies have linked deficiencies of micronutrients, including vitamin A and zinc to hearing impairment [4].…”
Section: Introductionmentioning
confidence: 99%